Implementation Of Predictive Policing By Kamneg Unit Of Satintelkam Pemalang Police Resort To Optimize The Prevention Of The Crime Of Weighted Theft - Nurochim, Maruf (Advances in Police Science Research Journal, 2024)
The focus of research in this final project is the implementation of predictive policing in order to optimize the prevention of criminal acts of weighted theft. The focus of this research is considered important because the number of weighted theft crimes in Pemalang Regency tends to increase even when the number of disturbances to the overall security and order has decreased in the past year. Therefore, the Pemalang Police's Satintelkam seeks to optimize the prevention of the crime of weighted theft, one of which is through the implementation of predictive policing in crime prevention. This study aims to: (1) describe the implementation of the prevention of criminal acts of weighted theft by the Unit Kamneg Satintelkam Pemalang Police Resort, (2) describe the implementation of predictive policing in preventing criminal acts of weighted theft by the Unit Kamneg Satintelkam PemalangPolice Resort. In the conceptual literature to analyze the problems above, several concepts are used as the basis for understanding, namely; Intelligence concept, Crime Prevention concept, Optimal concept, Theft with Weighting concept, and Predictive Policing concept. While the theory used in this study, namely; POAC Management theory, SWOT Analysis theory, and Implementation theory. In this study used qualitative methods with descriptive analysis to process data and field research (field research) to obtain data directly by participant-observation. Primary and secondary data sources use data triangulation to obtain data validity. The findings during this study were (1) The implementation of crime prevention by the Unit of the State Security and Security Unit, which was carried out through early detection, was still not optimal, the implementation of early detection was not in accordance with Perkabik No. 1 of 2013 concerning Intelligence Investigation. (2) The implementation of predictive policing is still not optimal because there is a misconception that predictive policing is applied to the real concept. The conclusions in this final project are, (1) Early detection is still not optimal, it still needs adjustments to Perkabik No.1 of 2013. (2) There must be an equalization of perceptions regarding the concept of predictive policing to all personnel so that it can be implemented in tasks to optimize crime prevention.